Thermogravimetric characterization of tyrosine and catechol adsorbed on montmorillonite. Issue 6 (2nd November 2018) - Rangel-Porras, Gustavo; Moncada-Sánchez, Cristina; Zárraga-Nuñez, Ramón; Romero-Toledo, Rafael; Miranda-Áviles, Raúl
ABSTRACT: Thermogravimetric analysis is suggested as an essential methodology for studying the interaction between montmorillonite-type clays and organic molecules such as amino acids and phenolic compounds. In this work, two commercial clays, a bentonite and a montmorillonite commercially called K10, were separately put in contact with solutions of catechol and tyrosine. After the contact with the organic molecules, the powders were characterized by X-ray diffraction, infrared spectroscopy, nitrogen adsorption at 77 K, scanning electron microscopy, and thermogravimetric analysis. The thermal stability of the organic molecules on the particles' surface depended mainly on the type of the montmorillonite clay used. This characteristic can be associated with the adsorption strength. The results show the importance of the thermogravimetric analysis for choosing the appropriate clay to be used in environmental studies or in the elaboration of industrial materials.